Temperature dependent piezoelectric response and strain–electric-field hysteresis of rare-earth modified bismuth ferrite ceramics. Issue 33 (8th August 2016) - Walker, Julian; Ursic, Hana; Bencan, Andreja; Malic, Barbara; Simons, Hugh; Reaney, Ian; Viola, Giuseppe; Nagarajan, Valanoor; Rojac, Tadej
Abstract : The specific rare-earth species substituted into BiFeO3 influences the phase composition, domain structure, strain–electric-field behavior and piezoelectric response at elevated temperatures. Abstract : The rare-earth (RE)-modified bismuth ferrite (BiFeO3 or BFO) family of ferroelectrics have uncomplicated lead-free chemistries and simple perovskite structures. Due to the high Curie transition temperature of the parent BiFeO3 perovskite (∼830 °C), they are promising piezoelectric materials for use at elevated temperatures. However, the influence of the specific RE species on the electromechanical behavior at high temperatures and above the coercive electric-field is not widely reported. Here, structural analysis over multiple length scales using X-ray diffraction, transmission electron microscopy and piezoresponse force microscopy is coupled with a high electric-field cycling study and in situ converse d 33 measurements up to 325 °C for three RE–BFO ceramic compositions, Bi0.86 Sm0.14 FeO3, Bi0.88 Gd0.12 FeO3 and Bi0.91 Dy0.09 FeO3 . The ceramics exhibit different phase assemblages with varying amounts of polar rhombohedral R 3 c and intermediate antipolar orthorhombic Pbam phases as a function of the RE species. During electric-field cycling at electric-fields with amplitudes of 160 kV cm −1, peak-to-peak strains of 0.23–0.27% are reached for all three compositions. However, there are qualitative differences in the field-induced strain and electric current behavior as a function of electric-field cycling and the materials exhibit an electrical-history dependent behavior. Bi0.91 Dy0.09 FeO3 possesses an improved d 33 stability as a function of temperature relative to the parent BFO perovskite and the highest depolarization temperature among the three RE–BFO compositions, with a stable d 33 of ∼22 pC N −1 up to 325 °C.